STRENGTHENING BUDGETARY CONTROL FOR FISCAL STABILITY IN UZBEKISTAN (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article discusses the importance of developing robust budgetary control mechanisms in Uzbekistan to ensure fiscal stability and sustainable economic growth. this article explores the current state of budgetary control in Uzbekistan, proposes strategies for improvement, and highlights the potential benefits of effective budgetary control for the nation's financial well-being.